Ways of walking: understanding walking's implications for the design of handheld technology via a humanistic ethnographic approach - Eslambolchilar, Parisa; Bødker, Mads; Chamberlain, Alan (Agora Center, University of Jyväskylä, 2016)
It seems logical to argue that mobile computing technologies are intended for use “on-the-go.” However, on closer inspection, the use of mobile technologies pose a number of challenges for users who are mobile, particularly moving around on foot. In engaging with such mobile technologies and their envisaged development, we argue that interaction designers must increasingly consider a multitude of perspectives that relate to walking in order to frame design problems appropriately. In this paper, we consider a number of perspectives on walking, and we discuss how these may inspire the design of mobile technologies. Drawing on insights from non-representational theory, we develop a partial vocabulary with which to engage with qualities of pedestrian mobility, and we outline how taking more mindful approaches to walking may enrich and inform the design space of handheld technologies.